2013
DOI: 10.1007/s10584-013-0828-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of climate change and increased atmospheric CO2 on hydrological and nitrogen cycling in an intensive agricultural headwater catchment in western France

Abstract: Climate change and increased atmospheric CO2 concentration can impact hydrological and nitrogen cycling at the catchment scale. The objective of this study is to assess these impacts in an intensive agricultural headwater catchment in western France. A calibrated and validated agro-hydrological model was driven by output of the climate model ARPEGE under the A1B emission scenario over 30-year simulation periods. Our study indicated that with climate warming and increased atmospheric CO2, the main trends in wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…Nonetheless, the magnitude of the mean increase in AirTemp (<0.04°C•year −1 ) was much lower than annual thermal fluctuations (8.11°C). It also suggested that climate change would influence primarily the seasonal distribution of hydroclimatic variations, which is likely to intensify both wet and dry periods, in line with previous studies (Chang et al, 2001;Gombault et al, 2015;Salmon-Monviola et al, 2013;Wang et al, 2018), or increase storm event frequency (not significant). Disentangling the human (agricultural) and climatic drivers of concentration trends was not possible here, but their respective effects appeared to be synergistic.…”
Section: Climatic Drivers Of Stream Concentration Dynamicssupporting
confidence: 82%
“…Nonetheless, the magnitude of the mean increase in AirTemp (<0.04°C•year −1 ) was much lower than annual thermal fluctuations (8.11°C). It also suggested that climate change would influence primarily the seasonal distribution of hydroclimatic variations, which is likely to intensify both wet and dry periods, in line with previous studies (Chang et al, 2001;Gombault et al, 2015;Salmon-Monviola et al, 2013;Wang et al, 2018), or increase storm event frequency (not significant). Disentangling the human (agricultural) and climatic drivers of concentration trends was not possible here, but their respective effects appeared to be synergistic.…”
Section: Climatic Drivers Of Stream Concentration Dynamicssupporting
confidence: 82%
“…The performance of the TNT2 and CASIMOD'N models to simulate observed behaviour of the two study catchments and other similar systems have been detailed in previous studies (Oehler et al 2009;Ferrant et al 2011;Moreau et al 2012bMoreau et al , 2013aBenhamou et al 2013;Salmon-Monviola et al 2013). Moreover, a detailed sensitivity analysis of TNT2 has been performed recently (Moreau et al 2013b).…”
Section: Resultsmentioning
confidence: 96%
“…However, computer simulations of this watershed by Salmon‐Monviola et al . [], based on future climate projections, predicted that spring and summer groundwater recharge and annual discharge will decrease between 1961 and 2099. Combined with these predictions, our results may indicate that mean annual DOC concentrations will increase in the future.…”
Section: Discussionmentioning
confidence: 98%